User Experience Analysis of the Users Babacucu.Com - Taruna Diyapradana; Ditdit Nugeraha Utama; Ahmad Nurul Fajar; Gunawan Wang (IAES Indonesia Section, 2018)
The Internet has made sharing information easier. By extension, it has also made sharing things easier. The problem is gauging the user experience of free E-commerce websites such as Babacucu.com to see whether people are interested to visit it or not. One of the elements of user experience is usability, that will be measured in this research. The methods used to measure the usability are questionnaires and usability testing with the users of Babacucu as subjects. The results of this study are the level of usability of Babacucu.com and recommendations on how to improve the site's usability.